Analisis Performansi Jaringan Indoor 4G LTE Di Gedung Admisi Universitas Muhammadiyah Yogyakarta - Aziz Yulianto Pratama; Widyasmoro Widyasmoro; Anna Nur Nazilah (CV. Syntax Corporation Indonesia, 2022)
Analysis performance of Indoor network 4G LTE is required at the admissions building of Muhammadiyah University of Yogyakarta which is a new building or building at UMY. This research is done by way of test drive using G-net track pro application that bought in google play store. Drive test method in G-net track pro application to know signal quality based on KPI standard that shows RSRP, RSRQ and SNR values by knowing from the result of color display on G-net track pro application. In the research results show that the building admisi is still need a strong signal improvement as well as the quality of the network / signal because the signal strength in the building is less than the maximum. From the research results prove that the ground floor, 1st Floor and 2nd Floor is the value of RSRP, RSRQ and SNR its value every higher the value of the RSRP its better but the RSRQ and SNR value is getting worse. The average value of RSRP value is green in value is -80 dBm s / d -90 dBm quality under normal conditions, RSRQ value is orange-the value is -10 dB s / d -14 dB where it is found that the quality is in bad condition, and SNR value is orange in the value of -5 dB s / d 0 dB where it is found that the quality is in bad condition. From the results of these data can be seen that the building admisi still need improvement of signal or network quality by doing a design and installation of indoor antenna